An effective teaching model for public school teachers in the Sultanate of Oman: students' stance - Al Barwani, Thuwayba Ahmad; Thabit Al-Ani, Wajeha; Amzat, Ismail Hussein (Emerald Group Publishing Limited, 2012)
Purpose – The purpose of this paper is to investigate what is the most important characteristic that leads to effective teaching in the general education schools in Oman, as perceived by the students.